The utility of high-frequency 18 MHz ultrasonography for preoperative evaluation of acral melanoma thickness in Chinese patients - Yu, Nianzhou; Huang, Kai; Li, Yixin; Jiang, Zixi; Liu, Siliang; Liu, Yuancheng; Liu, Xiaowan; Chen, Zeyu; He, Renliang; Wei, Tianhong (Frontiers in Oncology, 2023)
Background Despite the increasing use of preoperative ultrasound evaluation for melanoma, there is limited research on the use of this technique for Acral Melanoma (AM). Methods This retrospective study analyzed the electronic medical records of patients who underwent preoperative evaluation for cutaneous melanoma maximum thickness using an 18 MHz probe and histopathological examination between December 2017 and March 2021 at the Department of Dermatology in Xiangya Hospital, Central South University. Results A total of 105 patients were included in the study. The mean tumor thickness was 3.9 mm (s.d., 2.3), with 63% of the specimens showing ulceration and 44 patients showing lymph node metastasis. The results showed a good correlation between the high-frequency ultrasonography (HFUS) and histopathological thickness measurements, with a Spearman’s correlation coefficient of 0.83 [(95% CI 0.73–0.90) (P < 0.001)]. The positive predictive value (PPV) of sonography in identifying tumor thickness was also found to be high. Conclusion Our study suggests that high-frequency 18 MHz ultrasonography is an effective tool for the preoperative evaluation of AM thickness. The HFUS measurements correlated well with the histopathological thickness measurements, making it a valuable and reliable method for clinicians to assess the thickness of melanoma lesions preoperatively.